THE SYMBOL OF THE BUD IN THE WORKS OF ERKIN VAHIDOV (Neo Scientific Peer Reviewed Journal, 2023)
This article discusses the reflection of the image of the bud found in the work of the Hero of Uzbekistan Erkin Vahidov.